Zizo extra : hoera çavaria bestaat 40 jaar : dossier. - Aerts, Yves; De Roover, Dennis; Schazer, Elisa; Querton, Marc; Scheers, Thierry (Gent : ZiZo, 2017)
Fonds Suzan Daniel (FSD)
Nederlands
Brochure